2014
DOI: 10.1088/1748-9326/9/11/114019
|View full text |Cite
|
Sign up to set email alerts
|

Achieving accurate simulations of urban impacts on ozone at high resolution

Abstract: The effects of urbanization on ozone levels have been widely investigated over cities primarily located in temperate and/or humid regions. In this study, nested WRF-Chem simulations with a finest grid resolution of 1 km are conducted to investigate ozone concentrations [O 3 ] due to urbanization within cities in arid/semi-arid environments. First, a method based on a shape preserving Monotonic Cubic Interpolation (MCI) is developed and used to downscale anthropogenic emissions from the 4 km resolution 2005 Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
0
18
0
1
Order By: Relevance
“…Chemical transport models (CTMs) are increasingly common in simulating atmospheric chemical and transport processes at regional/continental/global scales because of the detailed physical and chemical processes which they are capable of simulating. For example, using a CTM (GFDL AM3), Lin et al (2012) found that Asian O 3 pollutants can affect surface [O 3 ] in the western US, contributing up to 8-15 ppbv to the DMA8; and that Asian pollution increases the DMA8 O 3 exceedance days by 53 % in the southwestern US. Huang et al (2013) combining model simulations at 12 km resolution (WRF/STEM), remote-sensing, and ground-based observations, have studied the effect of Southern California anthropogenic emissions (SoCal) on ozone pollution in southwestern US mountain states.…”
Section: J LI Et Al: Regional-scale Transport Of Air Pollutantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical transport models (CTMs) are increasingly common in simulating atmospheric chemical and transport processes at regional/continental/global scales because of the detailed physical and chemical processes which they are capable of simulating. For example, using a CTM (GFDL AM3), Lin et al (2012) found that Asian O 3 pollutants can affect surface [O 3 ] in the western US, contributing up to 8-15 ppbv to the DMA8; and that Asian pollution increases the DMA8 O 3 exceedance days by 53 % in the southwestern US. Huang et al (2013) combining model simulations at 12 km resolution (WRF/STEM), remote-sensing, and ground-based observations, have studied the effect of Southern California anthropogenic emissions (SoCal) on ozone pollution in southwestern US mountain states.…”
Section: J LI Et Al: Regional-scale Transport Of Air Pollutantsmentioning
confidence: 99%
“…We chose WRF-Chem (version 3.5.1) as the CTM since it has been successfully used in this region (Chen et al, 2013;Li et al, 2014;Zhao et al, 2012). In WRF-Chem, the Weather Research and Forecasting (WRF) model (Skamarock et al, 2008) is employed to resolve atmospheric physics and dynamical processes, while the coupled chemistry (Chem) model is used to simulate chemical processes such as gaseous and aqueous chemical reactions, dispersion, and deposition.…”
Section: Wrf-chem Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the most direct evidence of urbanization, characterized as the urban heat island (UHI) effect, is manifest as higher urban temperatures relative to rural (or undeveloped) areas (Arnfield 2003;Brazel et al 2000;Oke 1973), the effect of cities is more widespread. In addition to their direct alteration of local and regional climates, urban areas increase energy consumption (Salamanca et al 2014), negatively impact human comfort and raise heat stress within already hot environments (Hondula et al 2014;Yang et al 2014), can promote air quality degradation (Georgescu 2015;Li et al 2014), and have profound impacts on indoor thermal environments (Sailor 2014;Taleghani et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The most direct effect of UHI is lower thermal comfort of people in urban spaces, where there is no access to air conditioning systems [7][8][9][10][11]. UHI indirectly increases energy consumption for cooling [12,13], reduces the air quality in cities [14][15][16][17][18], and threats the ecosystem by warmer water flowing from the cities [19,20].…”
Section: Introductionmentioning
confidence: 99%